2011
DOI: 10.4269/ajtmh.2011.10-0246
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Model of Meningoencephalomyelitis by Rocio Flavivirus in Balb/C Mice: Inflammatory Response, Cytokine Production, and Histopathology

Abstract: Rocio virus (ROCV) is a flavivirus, probably transmitted by Culex mosquitoes and maintained in nature as a zoonosis of wild birds. Rocio virus caused a human epidemic of severe encephalitis that lasted from 1973 to 1980 in the Ribeira valley, in the southeastern coast of Brazil. After this outbreak, serologic evidence of ROCV circulation has been reported and public health authorities are concerned about a return of ROCV outbreaks in Brazil. We show here a study on the pathogenesis and the physiopathology of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 28 publications
5
19
0
Order By: Relevance
“…Despite its potential for further geographical spread, little is known about ROCV pathogenesis. In a mouse model of ROCV infection, a high virus titer was detected in the brain, and an elevated number of inflammatory macrophages was found in the central nervous system (CNS) [13,14], implying a role for macrophages during infection. However, further details on the role of these cells in the pathogenesis of ROCV have not been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its potential for further geographical spread, little is known about ROCV pathogenesis. In a mouse model of ROCV infection, a high virus titer was detected in the brain, and an elevated number of inflammatory macrophages was found in the central nervous system (CNS) [13,14], implying a role for macrophages during infection. However, further details on the role of these cells in the pathogenesis of ROCV have not been reported.…”
mentioning
confidence: 99%
“…The CNS contains resident innate immune sentinels such as microglia that are among the first responders to infection, but peripheral leukocytes, including monocytes, and T cells, are nevertheless recruited to aid in local inflammatory responses. These cells are reported to play a role in neurotropic viral infections, including those due to WNV, coronavirus (mouse hepatitis virus), and herpes simplex virus type 1 [13][14][15][16][17]. In addition, migration of monocytes to the brain is heavily dependent on the interaction between CCL2 and its receptor, CCR2 [18][19][20].…”
mentioning
confidence: 99%
“…24 A chronic persistence infection was also observed after intraperitoneal infection of ROCV into golden hamsters in which virus replicated and was excreted continuously. 25 Recently, our group showed that severe encephalitis developed in BALB/C mice infected with ROCV and these mice had inflammatory cell infiltrates in the CNS, 21 which suggested that infection of the CNS recruits leukocytes, and that this recruitment generates tissue damage in an attempt to control infection.…”
Section: Discussionmentioning
confidence: 99%
“…27 Our group also reported the ability of ROCV to induce apoptosis in neurons, which caused neuronal death. 21 However, it was not possible to state if neuronal death was caused directly by viral replication or was a consequence of the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation